Covering the European Union - Cauwenberge, Anna van (Javnost (Ljubljana), 2009)
This article investigates the cross-national prevalence of five news frames in quality papers' coverage of the Treaty of Lisbon (EU Constitution). Three frames were identified in earlier studies: economic consequences, conflict, and human interest. Two additional frames were identified and composed: powerand nationalisation. During the seven-month period leading up to the signing of the Treaty of Lisbon (December 2007), we analysed 341 articles from four quality papers: Le Monde (France), De Volkskrant (The Netherlands), De Standaard (Dutch speaking community of Belgium), and Le Soir (French speaking community of Belgium). Our results show that although signifi cant differences between newspapers were found in the amount of framing, overall they reflected a similar pattern in the adoption of the news frames. The economic consequences frame, followed by the power frame, appeared most prominently in all of the newspapers' coverage. However, the conflict and nationalisation frames recurred in a significantly lesser degree. These fi ndings indicate that the meaning behind the EU Constitution as a symbol of supranational unity could have led to a shift from a domesticated, conflict oriented coverage as found in previous studies to a more unified portrayal of the EU within and between the quality papers under study.
Keywords: European Union; Evropska unija; integracija; informiranje; časniki; časopisi; journalism; novinarstvo